Assessment of thrombectomy procedure difficulty by neurointerventionalists based on vessel geometry parameters from carotid artery 3D reconstructions - Shazeeb, Mohammed Salman; Moholkar, Viraj; King, Robert M.; Vedantham, Srinivasan; Vardar, Zeynep; Kraitem, Afif; Lindsay, Clifford; Anagnostakou, Vania; Singh, Jasmeet; Massari, Francesco; de Macedo Rodrigues, Katyucia; Naragum, Varun; et al. (Journal of clinical neuroscience, 2023)
•Patient vascular anatomy influences feasibility and ease of catheter navigation.•Little data on the influence of vessel metrics on target vessel access time exists.•AI use in CTA data reconstruction may predict feasibility of device navigation.•Need for scientific effort and technical development to facilitate the approach. Diagnosing and treating acute ischemic stroke patients within a narrow timeframe is challenging. Time needed to access the occluded vessel and initiate thrombectomy is dictated by the availability of information regarding vascular anatomy and trajectory. Absence of such information potentially impacts device selection, procedure success, and stroke outcomes. While the cervical vessels allow neurointerventionalists to navigate devices to the occlusion site, procedures are often encumbered due to tortuous pathways. The purpose of this retrospective study was to determine how neurointerventionalists consider the physical nature of carotid segments when evaluating a procedure’s difficulty. Seven neurointerventionalists reviewed 3D reconstructions of CT angiograms of left and right carotid arteries from 49 subjects and rated the perceived procedural difficulty on a three-point scale (easy, medium, difficult) to reach the targeted M1. Twenty-two vessel metrics were quantified by dividing the carotids into 5 segments and measuring the radius of curvature, tortuosity, vessel radius, and vessel length of each segment. The tortuosity and length of the arch-cervical and cervical regions significantly impacted difficulty ratings. Additionally, two-way interaction between the radius of curvature and tortuosity on the arch-cervical region was significant (p < 0.0001) wherein, for example, at a given arch-cervical tortuosity, an increased radius of curvature reduced the perceived case difficulty. Examining the vessel metrics and providing detailed vascular data tailored to patient characteristics may result in better procedure preparation, facilitate faster vessel access time, and improve thrombectomy outcomes. Additionally, documenting these correlations can enhance device design to ensure they suitably function under various vessel conditions.